2011
DOI: 10.1073/pnas.1010042108
|View full text |Cite
|
Sign up to set email alerts
|

Enteric commensal bacteria potentiate epithelial restitution via reactive oxygen species-mediated inactivation of focal adhesion kinase phosphatases

Abstract: The mechanisms by which enteric commensal microbiota influence maturation and repair of the epithelial barrier are relatively unknown. Epithelial restitution requires active cell migration, a process dependent on dynamic turnover of focal cell-matrix adhesions (FAs). Here, we demonstrate that natural, commensal bacteria stimulate generation of reactive oxygen species (ROS) in intestinal epithelia. Bacteria-mediated ROS generation induces oxidation of target cysteines in the redox-sensitive tyrosine phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 43 publications
(47 reference statements)
6
119
0
2
Order By: Relevance
“…We have shown that several species of normal human gut bacteria can induce rapid, "deliberate" generation of ROS within epithelial cells (23), and this ROS production has significant signaling effects on innate immunity, proliferation, and epithelial movement and restitution (19,29). Indeed, data in invertebrates suggest that ROS generation for signaling and microbiocidal functions in the gut epithelia may represent the ancestral form of response to bacteria (30).…”
Section: The Microbiota and Tissue Effects: Innate Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that several species of normal human gut bacteria can induce rapid, "deliberate" generation of ROS within epithelial cells (23), and this ROS production has significant signaling effects on innate immunity, proliferation, and epithelial movement and restitution (19,29). Indeed, data in invertebrates suggest that ROS generation for signaling and microbiocidal functions in the gut epithelia may represent the ancestral form of response to bacteria (30).…”
Section: The Microbiota and Tissue Effects: Innate Immune Regulationmentioning
confidence: 99%
“…In addition, individual members of the microbiota are able to actively modulate signaling intensity. A variety of reports have described commensals-many employed as probiotics-that are able to suppress eukaryotic inflammatory signaling pathways such as NF-kB and block inflammatory effector functions (19).…”
Section: The Microbiota and Tissue Effects: Innate Immune Regulationmentioning
confidence: 99%
“…The laboratory mouse has been instrumental for establishing roles for the gut microbiota in many aspects of mammalian physiology: angiogenesis (Stappenbeck et al 2002;Reinhardt et al 2012), bone mineral density (Cho et al 2012;Sjö gren et al 2012), brain development and behavior (Sudo et al 2004;Bravo et al 2011;Diaz Heijtz et al 2011;Ezenwa et al 2012), obesity and malnutrition Smith et al 2013), hepatic function (Dapito et al 2012;Henao-Mejia et al 2012), intestinal response to injury and repair (Rakoff-Nahoum et al 2004; Swanson et al 2011), and innate and adaptive immune function (for reviews, see Garrett et al 2010b;Littman and Pamer 2011;Hooper et al 2012). Ninety-nine percent of mouse genes are shared with humans at the host genetic level, and they share key similarities with the human gut microbiome at the phylum through family levels ( Fig.…”
Section: Micementioning
confidence: 99%
“…Mass spectrometry analysis has revealed that redox-sensitive thiolates are present in a limited subset of enzymes. Examples include protein tyrosine phosphatases (PTP) [65], the lipid phosphatase (PTEN) [62,66], MAP kinase phosphatases (MAPKP) such as DUSP3 [63], and lowmolecular-weight protein tyrosine phosphatases (LMW-PTP) [67], in enzymes involved in the sumoylation and neddylation reactions, and well as in oxidant sensors such as Keap1, which control of overall redox balance of the cell. (Figure 1).…”
Section: Redox Signaling and The Oxidation Of Reactive Cysteine Residuesmentioning
confidence: 99%